PELATIHAN PERAWATAN KENDARAAN SEPEDA MOTOR BAGI MASYARAKAT DESA SIRNAJAYA - Alfriana, Geovano; Cahyati, Aridewi; Putra, Purnama (Universitas Islam 45 Bekasi, 2024)
A motorcycle is an engine-driven two-wheeled vehicle composed of different parts that are subjected to different loads during operation, such as heat load, chemical load, impact, bump, twist, push-pull-bend force, friction, pressure. The precision of vehicle components will vary from their original and standard conditions over time such as becoming looser, weaker, or finer. To ensure it is always in top condition, cars require regular maintenance which can be done by a garage or by yourself. In improving the ability to maintain motorcycles and make an income through their own business, especially in the field of motorcycle maintenance services. Through this community service project, counseling on business management and training on motorcycle maintenance skills, including the correct adjustment and use of repair equipment, are provided. The service method applies socialization of motorcycle maintenance theory and direct assistance on how to perform motor vehicle maintenance for Sirnajaya Village youth. The results of this service activity are the increased knowledge, understanding, and abilities of the participants in the field of motorcycle maintenance and repair, besides that this service program supports the success of the community in establishing their own business.